Research of radio-frequency weights – spectrometers - Khizirova, M.A.; Grigor’eva, P.T. (Recent Contributions to Physics, 2012)
In this work was discussed a problem of possibility of removal of the pointed are defects of radiofrequency mass-spectrometers by replacing of the grid selective cascades by single lenses with along focus distance.